RETHINKING UKRAINE THROUGH MODERN AMERICAN CINEMATOGRAPH - Накашидзе, Ирина; Радкевич, Татьяна (SWorldJournal, 2020)
20th and beginning of 21st century are very hard and tragic for Ukrainian people. Until obtaining independence Ukraine was known as part of Soviet Union and many other countries there had been no distinction between Ukraine and Russia. Events in contempo